Collective values, behavioural norms, and rules: Building institutions for economic growth and poverty reduction - Ke-young Chu (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2001)
Economic growth and poverty reduction require for a country to establish efficient rules for economic and political transactions. Poor countries suffer from inadequate, inefficient transaction rules. Formal rules (e.g., laws, policies) must be nested in hospitable behavioural norms and values. Cultural collectivism in many of these countries and consequent group-oriented values, factionalism, and discretionary rule implementation have adverse implications for their efforts to establish well-defined property rights and other rules. Over time, these countries must establish rules for government-enforced, widespread impersonal transactions. To this end, efficient economic and political transactions should be promoted as repeated games. Institutional reform efforts should be aimed at expanding transactions, initially among small, voluntary groups, capitalizing on economic agents' group-oriented values for intragroup governance; at entrusting important rule implementing functions to autonomous, nonpoliticized agencies; and at inducing competing political groups to align their goals more with societal than factional interests. – growth ; poverty ; rules ; institutions ; human behaviour
Keywords: D70; H10; I30; K00; O10; Z10; 330; Wirtschaftswachstum; Armut; Institutionalismus; Public Choice; Theorie